2023
DOI: 10.1101/2023.11.02.565304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virological characteristics of the SARS-CoV-2 BA.2.86 variant

Tomokazu Tamura,
Keita Mizuma,
Hesham Nasser
et al.

Abstract: In late 2023, a lineage of SARS-CoV-2 emerged and was named the BA.2.86 variant. BA.2.86 is phylogenetically distinct from other Omicron sublineages identified so far, displaying an accumulation of over 30 amino acid mutations in its spike protein. Here, we performed multiscale investigations to reveal the virological characteristics of the BA.2.86 variant. Our epidemic dynamics modeling suggested that the relative reproduction number of BA.2.86 is significantly higher than that of EG.5.1. Experimental studies… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
2
17
1
Order By: Relevance
“…Our results have mixed correspondence with previous studies and data on XBB.1.5 and BA.2.86 (10,40,41,44,46,47). There are many potential explanations for our lack of statistically significant differences.…”
Section: Resultscontrasting
confidence: 79%
“…Our results have mixed correspondence with previous studies and data on XBB.1.5 and BA.2.86 (10,40,41,44,46,47). There are many potential explanations for our lack of statistically significant differences.…”
Section: Resultscontrasting
confidence: 79%
“…For example, vaccinated individuals who had breakthrough infection with different variants mount nAb response primarily towards the wildtype spike protein (9,10,14,18,21,26,27). In this study, all JN.1 patients in the infected cohort had received some doses of vaccine containing the WT spike (Table S1).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we discovered that the newly emerged BA.2.87.1 variant possesses an increased sensitivity to neutralization by these sera compared to JN.1, implying that this variant may not be able to outcompete the current JN.1 and become predominant. However, given that a single L455S mutation in the spike of JN.1 can dramatically increase the nAb evasion of BA.2.86 (3,14,21), there is a possibility that additional mutations in BA.2.87.1 could similarly result in new variants that dramatically enhance the nAb escape.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive multiscale investigations of the virological characteristics of the BA.2.86 variant demonstrated that the ACE2 binding affinity of BA.2.86 S RBD was comparable to that of XBB.1.5 S RBD and significantly higher than those of the ancestral B.1.1, XBB.1, XBB.1.16, EG.5.1 and the parental BA.2 variants. 56 This illuminating study showed that fusogenicity of the S protein of BA.2.86 and BA.2 were comparable, but the intrinsic pathogenicity of BA.2.86 was significantly lower than that of BA.2, suggesting that the attenuated pathogenicity of BA.2.86 may be due to its decreased replication capacity. 56…”
Section: Introductionmentioning
confidence: 83%